The dubious role of institutions in international business: A road forward - Aguilera, Ruth V.; Grøgaard, Birgitte (Journal of International Business Studies, 2019)
Our commentary returns to the conundrum of how institutions matter in international business (IB) by revisiting the 2018 JIBS Decade Award article by Jackson and Deeg (2008) on Comparing Capitalisms. We first synthesize their main insights around institutional diversity and track its significant impact within IB and other management fields. We then suggest three main takeaways that could move Jackson and Deeg’s agenda further in terms of developing a more nuanced approach to institutions in IB. We close with suggestions for future research and urge IB scholars to be more cautious when drawing on different strands of institutions theory.